Analisis Peran Lingkungan Kerja Dan Cyberloafing Terhadap Performa Karyawan Perusahaan Pengendalian Dan Perlindungan Mesin Manufaktur - Sutrisno Sutrisno; Hendy Tannady; Deddy Novie Citra Arta; Anugriaty Indah Asmarany; Leo Nardo Setia Budi Djojo (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to analyze whether related to cyberloafing and work environment on employee performance. The research model used is a quantitative method. This study consists of three variables namely, cyberloafing protection variables and free work environment variables, and employee performance variables as supporting variables. The data collection process was carried out using a questionnaire distributed to 100 respondents as a sample at PT. Putranata Adi Mandiri selected through simple random sampling technique. Data processing using IBM SPSS Version 20. The results of the study indicate that cyberloafing and work environment are positive and significant on employee performance. Cyberloafing behavior variables have a positive and significant effect on employee performance, and work performance variables are positive and significant on employee performance. Keyword: Cyberloafing Behavior, Wrok Enviroment, Employee Performance